Pricing Strategies – Comparative Analysis of Non-Exporting Enterprises and of Intense Exporters Based on the Example of Polish SMEs - Adam Oleksiuk (Studia i Materiały, 2021)
The research aim of the paper is to verify the differences with regard to the pricing strategies being implemented among non-exporting enterprises and intense exporters based on the example of Polish SMEs. The study presented was conducted between May – June 2019 on a representative sample of Polish SMEs created after 2004: non-exporters and exp orters with a min. 25% share of exports in the total sales. The research method applied is computer assisted web interviewing (CAWI) and computer assisted telephone interviewing (CATI). The total count of the sample is 240 businesses, randomly selected from a database which contains 2969 Polish companies. The study emphasizes that between exporting companies and non-exporting companies, there are differences in the pricing strategy application. Exporting enterprises more frequently have a differentiated pricing policy. No significant connection between the pricing strategy and the quality strategy was observed, both among non-exporting enterprises and intense exporters.